En route to local glioblastoma treatment with temozolomide doped hyaluronan fibres: formulation and in vitro cell studies - Belhajová, Marie; Vícha, Aleš; Burgert, Ladislav; Brožková, Iveta; Michalíčková, Ludmila; Moravec, Tomáš; Netuka, David; Musil, Zdeněk; Hrdina, Radim (ROYAL SOC CHEMISTRY, 2023)
We report the preparation, characterisation and in vitro tests of hyaluronan fibres containing up to 50 w/w% of temozolomide for local glyoblastoma treatment. These fibres form a hydrogel upon contact with cerebrospinal fluid on the treatment spot.
Na cestě k léčbě lokálního glioblastomu hyaluronanovými vlákny dopovanými temozolomidem: formulace a buněčné studie in vitro.
Keywords: hyaluronan fibres; temozolomide; glioblastoma treatment; hyaluronanová vlákna; temozolomid; léčba glioblastomu